Surface ionization of organic compounds on the basis of nitrogen, sulfur, phosphorus, and arsenic - S. A. Solntsev; K. O. Nagornov; V. I. Kapustin (Тонкие химические технологии, 2011)
A research facility and a technique for measuring the basic parameters of surface ionization of organic compounds were developed. For a series of organic compounds of nitrogen, sulfur, phosphorus, and arsenic the key parameters of surface ionization were determined.